Nano-Pektin sebagai Nanomaterial Pangan: Tinjauan Kritis tentang Preparasi dan Karakterisasinya: Nano‐Pectin as a Food Nanomaterial: A Critical Review of Its Preparation and Characterization - Yoedi Wicaksono; Yohan Ariesto; Prima Yaumil Fajri; Nazwa Nurhaliza (Jurnal Ilmiah Pangan Halal, 2026)
Pectin is a naturally occurring polysaccharide that could be produced, especially using nanotechnology techniques, as a functional biopolymer in food systems. The goal of converting pectin into nano-pectin is to increase its specific surface area, colloidal stability, and ability to encapsulate and transport bioactive substances. In order to assess the synthesis techniques, characteristics, benefits, and drawbacks of nanopectin for food applications, this paper provides a critical literature assessment. The study was carried out using the PRISMA standards and a Scopus literature search for the years 2015–2025. Chemical alteration and physical engineering were the two primary methods that were examined. For Pickering emulsions, the chemical method via polyelectrolyte complexation yields small nanoparticles (~82 nm) with strong interfacial stability, but it has drawbacks in terms of food safety. On the other hand, despite restricted molecular structural control, the stepwise physical approach yields bigger nano-pectin (~278 nm) with potent antioxidant bioactivity, proven safety, and successful direct application in functional food products. Combining the two methods could result in nano-pectin that is stable, safe, and useful for contemporary culinary applications.